Large flexion contracture angle predicts tight extension gap during navigational posterior stabilized-type total knee arthroplasty with the pre-cut technique: a retrospective study - Takaaki Hiranaka; Shinichi Miyazawa; Takayuki Furumatsu; Yuya Kodama; Yusuke Kamatsuki; Shin Masuda; Yuki Okazaki; Keisuke Kintaka; Toshifumi Ozaki (BMC Musculoskeletal Disorders, 2022)
Abstract Background This study aimed to determine the predictors of tight extension gap (EG) compared with the flexion gap (FG) during navigational posterior stabilized-type total knee arthroplasty using the pre-cut technique. Methods Nineteen patients with tight EG (defined as FG-EG ≥2 mm after pre-cut; group T) and 84 patients with an approximately equal gap (defined as FG-EG = 0–1 mm after pre-cut; group E) were enrolled. Medial tibial slope angle, hip knee ankle angle, flexion contracture angle, and active maximum flexion angle were compared between the two groups. Results The multivariate logistic regression model indicated that the probability of tight EG increased with flexion contracture angle (odds ratio, 1.13; 95% confidence interval 1.05–1.20; P ≤ 0.001). According to the receiver operating characteristic analysis, the flexion contracture angle cut-off value associated with tight EG was 15.0° (sensitivity, 85%; specificity, 78%). Conclusion This study demonstrated that a large flexion contracture angle (cut-off 15.0°) was associated with tight EG after pre-cut osteotomy during posterior stabilized-type total knee arthroplasty. Awareness of this risk factor may help improve preoperative predictability of tight EGs and preparedness for additional procedures, such as soft tissue release or capsulotomy, to correct them. Level of evidence Level III.